Reportoire de la jurisprudence de la cour Internationale de Justice (1947-1992) : = Reportery of decisions of the International Court of Justice (1947-1992) - Capaldo, Giuliana Ziccardi (Dordrecht : Martines Nishoff Publishers, 1995)
2 volumes
Keywords: Arbitration International; International Courts; International Law